Selecting and assessing social objectives for Australian fisheries management. (March 2015) - Brooks, Kate; Schirmer, Jacki; Pascoe, Sean; Triantafillos, Lianos; Jebreen, Eddie; Cannard, Toni; Dichmont, Cathy M.
Abstract: This paper details Australian research that developed tools to assist fisheries managers and government agencies in engaging with the social dimension of industry and community welfare in fisheries management. These tools are in the form of objectives and indicators. These highlight the social dimensions and the effects of management plans and policy implementation on fishing industries and associated communities, while also taking into account the primacy of ecological imperatives. The deployment of these objectives and indicators initially provides a benchmark and, over the life of a management plan, can subsequently be used to identify trends in effects on a variety of social and economic elements that may be objectives in the management of a fishery. It is acknowledged that the degree to which factors can be monitored will be dependent upon resources of management agencies, however these frameworks provide a method for effectively monitoring and measuring change in the social dimension of fisheries management. Essentially, the work discussed in this paper provides fisheries management with the means to both track and begin to understand the effects of government policy and management plans on the social dimension of the fishing industry and its associated communities. Such tools allow the consideration of these elements, within an evidence base, into policy arrangements, and consequently provide an invaluable contribution to the ability to address resilience and sustainability of fishing industries and associated communities. Highlights: Addresses resilience and sustainability of fishing industry related communities. Provides objectives for, and indicators of, a fishery׳s social performance. Provides a means to understand the social effects of policy and management plans. Allows evidence-based consideration of the social effects of policy arrangements. Provides tools to address the social components of fisheries management ESD reporting.